2013
DOI: 10.1111/jir.12091
|View full text |Cite
|
Sign up to set email alerts
|

Where are persons with intellectual disabilities in medical research? A survey of published clinical trials

Abstract: The findings highlight the exclusion of persons with ID in medical research. Efforts are needed to increase inclusion through research policy initiatives and education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
114
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(119 citation statements)
references
References 42 publications
4
114
0
1
Order By: Relevance
“…We thus fund ourselves with too little information to address the pressing disparities experienced by people with intellectual disability, alongside conditions that threaten justice. To address tenacious disparities and promote human rights, we must respectfully and safely include people with intellectual disability in population-specific and general population research (Brooker et al, 2014; Feldman, Bosett, Collet, & Burnham-Riosa, 2013; Iacono & Carling-Jenkins, 2012; Northway, 2014; Welch et al, 2015). Righting past wrongs requires attention to promoting research benefits desired by community members (Dresser, 2014); importantly, like the general population, the prospect of direct and/or indirect benefits motivates adults with intellectual disability to participate in research (McDonald, Kidney, & Patka, 2012).…”
mentioning
confidence: 99%
“…We thus fund ourselves with too little information to address the pressing disparities experienced by people with intellectual disability, alongside conditions that threaten justice. To address tenacious disparities and promote human rights, we must respectfully and safely include people with intellectual disability in population-specific and general population research (Brooker et al, 2014; Feldman, Bosett, Collet, & Burnham-Riosa, 2013; Iacono & Carling-Jenkins, 2012; Northway, 2014; Welch et al, 2015). Righting past wrongs requires attention to promoting research benefits desired by community members (Dresser, 2014); importantly, like the general population, the prospect of direct and/or indirect benefits motivates adults with intellectual disability to participate in research (McDonald, Kidney, & Patka, 2012).…”
mentioning
confidence: 99%
“…Considerando además sus perfiles particulares de salud, es de esperar que tampoco reaccionen a los tratamientos de la misma forma que las personas sin TDI. 40 En general, los médicos carecen de formación sobre el cuidado y la atención de las personas con discapacidad, condición que puede comprometer la salud de este tipo de pacientes y contribuir a las disparidades en su atención. 41 Tener una información fiable de la realidad sanitaria es esencial para identificar las disparidades de salud, pero, en las encuestas de salud, las personas con TDI no suelen estar representadas.…”
Section: Atención Sanitariaunclassified
“…12 19 There are modifications and adaptations that can be made to study designs and procedures to minimise obstacles including accessible information materials (eg, easy-read formats were successfully used in WIELD-see online supplementary material), simplified consent procedures, modified procedures to allow support from carers and simplified data collection materials. 19 People with learning disabilities are positive about participating in research and highlight the importance of researchers understanding their experiences and opinions. 52 Two key factors in this study facilitated successful recruitment and high levels of acceptability of the design.…”
Section: Research In Contextmentioning
confidence: 99%
“…People with learning disabilities are often excluded from clinical trials19 resulting in a weak evidence base for effective treatment and services for this population. This is particularly evident in epilepsy research,12 illustrated by a recent review of service responses for epilepsy in learning disabilities which identified no evaluations using randomisation or a matched comparison group 15.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation